The combinatorial (19 sub 4) configurations - Osuna, Octavio Páez (Ars mathematica contemporanea, 2012)
A parallel backtrack search is carried out to classify, up to isomorphism, all combinatorial ?$(19_4)$? configurations. A total of 269 224 652 such configurations were found. We prove that two of the combinatorial ?$(19_4)$? configurations are not geometrically realizable over any field. Also we confirmed the computation of the 971 171 combinatorial ?$(18_4)$? configurations which lacked an independent verification.
Keywords: AMDS-Code; combinatorics; configurations; finite geometries; kombinatorika; končne geometrije; konfiguracije; parallel backtracting search with isomorph rejection; symmetric designs